Non‐Heme Dioxygenase Catalyzes Atypical Oxidations of 6, 7‐Bicyclic Systems To Form the 6, 6‐Quinolone Core of Viridicatin‐Type Fungal Alkaloids1. Issue 47 (22nd September 2014) - Ishikawa, Noriyasu; Tanaka, Hidenori; Koyama, Fumi; Noguchi, Hiroshi; Wang, Clay C. C.; Hotta, Kinya; Watanabe, Kenji
Abstract The 6, 6‐quinolone scaffold of the viridicatin‐type of fungal alkaloids are found in various quinolone alkaloids which often exhibit useful biological activities. Thus, it is of interest to identify viridicatin‐forming enzymes and understand how such alkaloids are biosynthesized. Here an Aspergillal gene cluster responsible for the biosynthesis of 4′‐methoxyviridicatin was identified. Detailed in vitro studies led to the discovery of the dioxygenase AsqJ which performs two distinct oxidations: first desaturation to form a double bond and then monooxygenation of the double bond to install an epoxide. Interestingly, the epoxidation promotes non‐enzymatic rearrangement of the 6, 7‐bicyclic core of 4′‐methoxycyclopenin into the 6, 6‐quinolone viridicatin scaffold to yield 4′‐methoxyviridicatin. The finding provides new insight into the biosynthesis of the viridicatin scaffold and suggests dioxygenase as a potential tool for 6, 6‐quinolone synthesis by epoxidation of benzodiazepinediones.